2017
DOI: 10.1021/acs.chemmater.7b00827
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Correlation between Carrier Mobility and Intermolecular Center-to-Center Distance in Organic Single Crystals

Abstract: Charge transport properties of organic semiconductors critically depend on their molecular packing structures. Controlling the charge transport in varying the molecular packing and understanding their structure-property correlations are essential for developing high-performance organic electronic devices. Here we demonstrate that the charge carrier mobility in organic single-crystal nanowires can be modulated with respect to the intermolecular center-to-center distance by applying uniaxial strain to the cofaci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 49 publications
2
8
1
2
Order By: Relevance
“…Notably, on the basis of our computed transfer integrals, hopping approaches such as Marcus theory are unable to reproduce the experimental trend, since the mobility is proportional to the square of the transfer integral value and the non‐monotonic trend in the transfer integral variation ( Figure ) would reflect in a non‐monotonic variation of mobility (e.g., 75% decrease with 1% elongation but 358% increase with 5% elongation, see Supporting Information), in clear contradiction with experimental reports. [ 31 ] This result confirms that comparing relative trends in charge mobility under the effect of different mechanical deformations is an ideal approach to highlight the main qualitative differences between theories.…”
Section: Resultssupporting
confidence: 71%
See 2 more Smart Citations
“…Notably, on the basis of our computed transfer integrals, hopping approaches such as Marcus theory are unable to reproduce the experimental trend, since the mobility is proportional to the square of the transfer integral value and the non‐monotonic trend in the transfer integral variation ( Figure ) would reflect in a non‐monotonic variation of mobility (e.g., 75% decrease with 1% elongation but 358% increase with 5% elongation, see Supporting Information), in clear contradiction with experimental reports. [ 31 ] This result confirms that comparing relative trends in charge mobility under the effect of different mechanical deformations is an ideal approach to highlight the main qualitative differences between theories.…”
Section: Resultssupporting
confidence: 71%
“…Our predicted relative variation of the mobility with strain is in very good agreement with experimental data in ref. [31]: our computations predict a monotonic increase in mobility up to 1979% (experimental 1854%) under 16% compression and a decrease up to 42% (experimental 97%) under 16% elongation. Notably, on the basis of our computed transfer integrals, hopping approaches such as Marcus theory are unable to reproduce the experimental trend, since the mobility is proportional to the square of the transfer integral value and the non‐monotonic trend in the transfer integral variation ( Figure ) would reflect in a non‐monotonic variation of mobility (e.g., 75% decrease with 1% elongation but 358% increase with 5% elongation, see Supporting Information), in clear contradiction with experimental reports.…”
Section: Resultsmentioning
confidence: 90%
See 1 more Smart Citation
“…This contrasts with TES‐pentacene which packs in a 1D slipped stack motif and gives an inferior OTFT mobility, compared with TIPS‐pentacene, despite its higher magnitude transfer integral of 94 meV . For TIPS‐pentacene the relationship between X‐ray crystallographic packing, transfer integrals, and mobility has been widely investigated . These comparisons are similar to those made for NFAs in this study.…”
Section: Resultssupporting
confidence: 70%
“…In the literature, it is reported that compressive strain along the π -π stacking distance reduces the molecular centerto-center distance, thus enhancing the charge transport in TIPS-pentacene and PTCDI-C8 [60]. However, our results for TIPS-pentacene indicates that the π -π stacking distance is nearly independent on the molecular center-to-center distance.…”
Section: Discussioncontrasting
confidence: 70%